Penerapan Nilai-Nilai Hadis Dalam Manajemen Krisis Digital - Galuh Prabowo (Jurnal Pendidikan Indonesia (JOUPI), 2024)
There is often a dissonance between religious values, as stated in the hadith, and modern business practices, especially in complex and rapidly changing digital crisis situations. The increasingly sophisticated digital technology today has made major changes to the world, giving birth to various types of increasingly advanced digital technologies. Various groups have been facilitated in accessing information in various ways, and can enjoy digital technology facilities freely and easily under control. The application of hadith values ​​can increase the effectiveness of digital crisis management. By integrating hadith values, organizations can respond to crises faster, more effectively, and more humanely. However, the challenge is that there is no comprehensive framework on how hadith values ​​can be effectively applied in digital crisis management. This study uses a qualitative approach by means of library research. The research approach is the analysis of texts and information related to the study. The data sources for this study are scientific books, journals, scientific research results, scientific study results, seminar results, and so on. From the results of the discussion, it can be concluded that knowing the most relevant hadith values ​​in the context of digital crisis management is an important step in building a better, stronger, and more sustainable company. By integrating religious values ​​into business practices, companies can make positive contributions to society and achieve long-term success.